2022
DOI: 10.3389/fimmu.2022.992630
|View full text |Cite
|
Sign up to set email alerts
|

Divergent outcomes of anti-PD-L1 treatment coupled with host-intrinsic differences in TCR repertoire and distinct T cell activation states in responding versus non-responding tumors

Abstract: Differential responses to immune checkpoint inhibitors (ICI) may be attributed to tumor-intrinsic factors or environmental cues; however, these mechanisms cannot fully explain the variable ICI responses in different individuals. Here, we investigate the potential contribution of immunological heterogeneity with a focus on differences in T-cell receptor (TCR) repertoire to ICI responses, which has not been defined previously. To reveal additional factors underlying heterogeneous responses to ICI, we employed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 66 publications
3
9
0
Order By: Relevance
“…We made a few unexpected discoveries (1): there were no differences in clonal expansion status or TCR diversity indexes between R vs. NR CD8 TILs (2); top expanded TCR clonotypes differed substantially, almost mutually exclusive, between R vs. NR CD8 TILs, when the threshold of clonal frequency was set as >1% or >0.5%. This observation is consistent with our previous single-cell sequencing results ( 19); (3) however, when clonotypes with lower frequencies were included, we failed to detect differences in TCR clonotypes between R vs. NR CD8 TILs, a finding not observed in our previous study (19). Basically, in the current study, we found that R clonotypes were also detected in NR recipients, albeit at a much lower frequency, and vice versa.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We made a few unexpected discoveries (1): there were no differences in clonal expansion status or TCR diversity indexes between R vs. NR CD8 TILs (2); top expanded TCR clonotypes differed substantially, almost mutually exclusive, between R vs. NR CD8 TILs, when the threshold of clonal frequency was set as >1% or >0.5%. This observation is consistent with our previous single-cell sequencing results ( 19); (3) however, when clonotypes with lower frequencies were included, we failed to detect differences in TCR clonotypes between R vs. NR CD8 TILs, a finding not observed in our previous study (19). Basically, in the current study, we found that R clonotypes were also detected in NR recipients, albeit at a much lower frequency, and vice versa.…”
Section: Discussionsupporting
confidence: 93%
“…injection three times (2-day interval) or PBS only as vehicle control (control group). Of note, as shown in our previous study (19), all the tumor-bearing mice in the control group had tumor growing out, and no substantial differences were observed in tumor growth among control group. To assess treatment effects, relative change in tumor volume (RCTV) was calculated as the change in tumor volume (TV) from the start of treatment (TV 0 ) to the TV at day n (the endpoint of control group) (TV n ) divided by TV 0 (RCTV=[TV n −TV 0 ]/TV 0 ).…”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations